2018
DOI: 10.1016/j.compstruct.2018.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Double lap adhesive joint with reduced stress concentration: Effect of slot

Abstract: Stress distributions at interfaces of adhesive lap joints have been widely studied to optimize overall structural strength. However, these studies focussed mainly on the mechanics of adhesive layers. In this paper, a novel concept for a double lap adhesive joint is proposed by introducing a slot in its inner adherend. Numerical simulations employing a finite-element method are used to validate the proposed concept. The results show that the introduction of the slots can smooth the stress distributions along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Roughly 400 elements were used for the cohesive region. This model was developed to be similar to previous works on adhesive joints [18], [19]. The model can be seen in Figure 7.
Figure 7FEM model of a simplified joint.
…”
Section: Methodsmentioning
confidence: 99%
“…Roughly 400 elements were used for the cohesive region. This model was developed to be similar to previous works on adhesive joints [18], [19]. The model can be seen in Figure 7.
Figure 7FEM model of a simplified joint.
…”
Section: Methodsmentioning
confidence: 99%
“…The effects of tapering adherends were investigated by Sancaktar and Nirantar [27]. Hou et al [28] have shown that the insertion of a defect in the internal adhesion of a double lap type joint led to a reduction of the stress peaks recorded at the edges of the adhesive region while reducing the overall weight of the joint.…”
Section: Problem Statementmentioning
confidence: 99%
“…In this paper the dynamic behavior of a DLJ is investigated, using an epoxy adhesive with both normal and cracked adherends, considering the geometries considered in literature [28]. The geometry is shown in Figure 1.…”
Section: Problem Statementmentioning
confidence: 99%
“…Peel stress is more critical to the adhesive lap joint compared with shear stress, since it is considered to dominate the failure of the joint [26]. The maximum peel stress is negative in section I, representing that the left end of the bonding region is subjected to a compressive load.…”
Section: Parametric Studymentioning
confidence: 99%
“…Moya-Sanz et al [25] developed a 2-D numerical model in the Abaqus/Standard to investigate the effects of geometry such as recessing and chamfering of the adherends and adhesive on the failure load of a single-lap joint under uniaxial tensile force, using the cohesive zone model. Hou et al [26] proposed a novel concept to reduce the stress concentration at both ends of the bonding region in a double lap joint by making a slot in the inner adherend using finite element numerical simulation. Santos et al [3] employed a numerical method based on XFEM to predict the stress distribution, strength and damage propagation in the adhesively bonded joints.…”
Section: Introductionmentioning
confidence: 99%